Analisis Bahan Sarang Burung Madu Sriganti (Cinnyris jugularis L.,1766) di Kawasan Kampus Universitas Syiah Kuala, Darussalam, Banda Aceh (Isolation and Analysis of Proteolytic Activity of Local Actinomycetes from Aceh, Indonesia) - Saida Rasnovi; Rahmi Fitriana; Aida Fithri; Rosi Wahyuni; Amalia Amalia (Jurnal Bioleuser, 2025)
The olive-backed sunbird (Cinnyris jugularis.L.,1766) is a species within the Nectarinidae family, a bird group that primarily feeds on nectar from various flowers. This study aimed to identify the types of nest materials, the composition of these materials, and the number of plant species used by C. jugularis to make nests. The results showed that olive-backed sunbird nest materials are composed of 14 types, consisting of 10 types of natural nest materials and 4 types of non-natural nest materials. Natural nest materials come from various parts of plants and animals, while non-natural nest materials include yarn, raffia, plywood, fiberboard, and paper. The most common and heaviest nest materials are those from plants (55%), animals (29%), and non-natural materials (16%). There are 11 plant species used as nest materials, the most widely used is the Casuarina equisetifolia